2017
DOI: 10.1007/s12325-017-0549-0
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Observational Post-Marketing Study of Tafluprost for Glaucoma and Ocular Hypertension: Effectiveness and Treatment Persistence

Abstract: Santen Pharmaceutical Co., Ltd., Osaka, Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 10 publications
6
11
1
Order By: Relevance
“…Our results are similar to short-term12 and long-term follow-up results13 from a large-scale post-marketing study in Japanese patients with glaucoma or OHT who initiated tafluprost treatment. The study by Kuwayama et al prospectively observed 4502 patients over a 2-year period in the real-world setting, collecting IOP and safety data.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results are similar to short-term12 and long-term follow-up results13 from a large-scale post-marketing study in Japanese patients with glaucoma or OHT who initiated tafluprost treatment. The study by Kuwayama et al prospectively observed 4502 patients over a 2-year period in the real-world setting, collecting IOP and safety data.…”
Section: Discussionsupporting
confidence: 86%
“…This suggests that the degree of IOP reduction may be directly proportional to the baseline untreated IOP. Overall, authors concluded that tafluprost showed significant long-term IOP-lowering effects regardless of treatment patterns or diagnosis, with minimum safety concerns in the actual clinical practice 13…”
Section: Discussionmentioning
confidence: 98%
“…However, the tafluprost treatment persistence in the present study was 86.4% for 24 months, which was similar to the data reported in another observational, non-interventional study. 12 There was no noticeable difference in patient backgrounds between the visual field analysis and safety analysis sets.…”
Section: Discussionmentioning
confidence: 89%
“…10 In post-launch observational studies, which followed for 2 years after treatment initiation, tafluprost showed a favorable IOP-lowering effect and safety profile in the daily clinical practice setting in patients with various types of glaucoma, including NTG. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…18,25,26 Tafluprost, a recent prostaglandin F 2α derivative, has demonstrated long-term intraocular pressure-lowering effects regardless of treatment patterns or diagnosis. 27 Tafluprost 0.0015% was formulated into two preparations; preserved and PF. Currently, preserved tafluprost is a prostaglandin eye drop, which contains the lowest concentration of BAK (0.001%) compared to other prostaglandin formulations containing preservatives.…”
Section: Introductionmentioning
confidence: 99%